Pengaruh Net Profit Margin, Earning Per Share, Dan Return On Asset Terhadap Harga Saham Perusahaan Properti Di Bei - Kenny Kenny (Universitas Tarumanagara, 2019)
This study aims to analyze factors that affect the stock price of property companies that are listed in BEI within a period between year 2012 to 2016. This research is a study to determine the influence between net profit margin, earning per share, and return asset towards stock price. The population used in this research are all property companies that are listed in BEI during the research period. The samples are collected by using the purposive sampling method. There are 17 companies that are used as samples for this research. This research used multiple linear regression, with t-statistic test, F-statistic test, and adjusted coefficient of determination to determine the truth about hypotheses. The result of this research are net profit margin has negative and significant effect on the stock price, while earning per share and return on asset has non-significant effect on the stock price. Together, Net Profit Margin, Earning Per Share, and Return On Asset have significant effect on stock price.